IL1RN and KRT13 Expression in Bladder Cancer: Association with Pathologic Characteristics and Smoking Status - Thomas S. Worst; Verena Reiner; Ute Gabriel; Christel Weiß; Philipp Erben; Thomas Martini; Christian Bolenz (Advances in Urology)
Purpose. To validate microarray data on cytokeratin 13 (KRT13) and interleukin-1 receptor antagonist (IL1RN) expression in urothelial carcinoma of the urinary bladder (UCB) and to correlate our findings with pathologic characteristics and tobacco smoking. Methods. UCB tissue samples (n=109) and control samples (n=14) were obtained from transurethral resection and radical cystectomy specimens. Immunohistochemical staining of KRT13 and IL1RN was performed and semiquantitative expression scores were assessed. Smoking status was evaluated using a standardized questionnaire. Expression scores were correlated with pathologic characteristics (tumor stage and grade) and with smoking status. Results. Loss of KRT13 and IL1RN expression was observed in UCB tissue samples when compared to controls (P=0.007, P=0.008) in which KRT13 and IL1RN expression were high. IL1RN expression was significantly reduced in muscle-invasive tumors (P=0.003). In tissue samples of current smokers, a significant downregulation of IL1RN was found when compared to never smokers (P=0.013). Conclusion. Decreased expressions of KRT13 and IL1RN are common features of UCB and are associated with aggressive disease. Tobacco smoking may enhance the loss of IL1RN, indicating an overweight of proinflammatory mediators involved in UCB progression. Further validation of the influence of smoking on IL1RN expression is warranted.